Variation of Subharmonic Function under Transformation of its Riesz Measure - Kudasheva, E. G.; Khabibullin, B. N. (Журнал математичної фізики, аналізу, геометрії, 2007)
The paper combines two aspects. First, it contains a compressed comparative review of the well-known results on the change of growth of entire (subharmonic resp.) function under the shifts of its zeros (under T-shift of its Riesz measure resp.). There was B.Ya. Levin who stood at the sources of these results. Second, the first coauthor proves new results obtained in thisdirection: the estimates of change of subharmonic function under integralrestrictions for T-shift of its Riesz measure, and also, in a certain sense, an optimal approximation of an entire function by the entire function with simple zeros.* Mathematics Subject Classification: 30D15, 31A05.